A Review on Heat Transfer and Fluid Flow Characteristics through Double-Pipe U-Tube HeatExchanger - Sonu Kumar Kushwaha (AG Volumes, 2021)
In the current context more and more efficient heat transfer system are required. The solution based on turbulent flow through heat exchangers has proven successful in terms of high heat transfer rate. All past studies on this topic was experimental based. The present approach is based on CFD (Computational Fluid Dynamics) technique. As a starting point, this study examines how various characteristics, such as the kind of fins, orientation, forms, and positions, might be used to optimise heat exchanger thermal performance. The purpose of this review is to explain how each of the parameters listed affects thermal performance.